Multi-timescale available flexibility assessment of integrated energy systems considering different proportions of wind power installations - Zhang, Song; Zhang, Yan; Li, Shuguang (Frontiers in Energy Research, 2024)
The available flexibility capacity of the integrated energy system can be used as one of the indicators of proportions of system wind power installations, which in turn affects the maximum installed capacity of the system wind power, and this paper proposes a method for assessing the available flexibility of the integrated energy system at multiple time scales considering different proportions of system wind power installations. First, the framework of the integrated energy system is constructed, and based on the coupling relationship between the electrical and thermal systems, the mathematical models of the P2G, CHP, energy storage equipment and wind power generation equipment within the integrated energy system are established, and the Monte Carlo method is used to predict the wind power output in a typical scenario; Secondly, an integrated energy system optimization model is constructed to obtain the optimal dispatch operation of the system; the empirical mode decomposition(EMD) algorithm is used to decompose the flexibility demand curve of the system in multiple time scales. The flexibility supply capacity model of different types of flexibility resources in the system at different time scales is established, and through the comparative analysis of flexibility supply and demand at the same time scale, the upward and downward flexibility shortage probability and shortage expectation indexes at each time scale can be intuitively calculated and then weighted to constitute a comprehensive index of system flexibility assessment. Finally, the available flexibility analysis of the integrated energy system under different installed wind power capacities shows that the proposed methodology can more comprehensively assess the available flexibility capacity of the integrated energy system under different time scales, and can obtain the maximum installed wind power capacity that the system can withstand while guaranteeing sufficient available flexibility capacity.